Architectural types and dimensions of spaces in social housing - Reis, Antônio Tarcísio da Luz (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The objective of this article is the comparison of built areas and open spaces in the original designs and in the occupied dwellings, between distinct housing estates and architectonic types, identifying growing and reduction of these areas, the number, type and areas of rooms; as well as the analysis of furniture and attitudes of residents concerning the dimensions of spaces in the housing unit and the importance of satisfaction with room size for the satisfaction with the housing unit. The methodology used as data gathering includes questionnaires and interviews, besides physical measurement in 374 housing units in 12 estates comprised by blocks of flats, terraced and detached houses located in the metropolitan area of Porto Alegre and occupied by a low-middle income population during the eighties and nineties. Data analysis includes the use of non-parametric statistical tests, such as the Kruskal-Wallis test of analysis of variance, Spearman rank correlation test and cross-tabulation. Among the main results are the growing and the inadequate size of some rooms, independently of the architectonic type analysed, making possible the indication of certain space dimensions that might respond satisfactorily to the residents.